Peter C. Peterson letter to Thomas Kent regarding Vireo and Warbler accounts and Fall birds sighted, November 30, 1980 - Petersen, Peter C.et al (1980)
Peter C. Peterson letter reports that the Vireo and Warbler accounts are done and includes a list of Fall bird sightings. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of Fall 1980. Epson - sheet feed/flatbed